Суперiнтегровнi системи з довiльним спiном - Nikitin, A. G. (Publishing house "Academperiodika", 2018)
Superintegrable quantum mechanical systems with spin are presented. These systems admit a generalized Laplace–Runge–Lenz vector and possess the dynamical symmetry with respect to group SO(4) for bound states. Our discussion is restricted mainly to 2d and 3d systems, but a special class of arbitrary dimension systems is presented as well.